Ambidexterity penetration across multiple organizational levels in an aerospace and defense organization. Issue 3 (June 2019) - Kassotaki, Olga; Paroutis, Sotirios; Morrell, Kevin
Abstract: The ambidexterity framework, which comprises two contradictory, yet interrelated processes of exploration and exploitation, has been researched using a variety of perspectives. Few studies, however, provide insight into the question: how is ambidexterity managed across multiple organizational levels? To address this question, we introduce the term ambidexterity penetration that refers to the enactment of ambidexterity across multiple organizational levels and develop a conceptual framework about how it is practiced ( horizontally, vertically and organizationally ). We empirically showcase this framework using findings from six business units of an aerospace and defense organization and analyzing data from 30 interviews. Overall, our study contributes to ambidexterity research and offers an empirical investigation of ambidexterity penetration across multiple organizational levels in the context of the aerospace and defense sector.